1995
DOI: 10.1152/jappl.1995.78.3.928
|View full text |Cite
|
Sign up to set email alerts
|

Gas density does not affect pulmonary acoustic transmission in normal men

Abstract: Fremitus, the transmission of sound and vibration from the mouth to the chest wall, has long been used clinically to examine the pulmonary system. Recently, modern technology has become available to measure the acoustic transfer function (TF) and transit times (TT) of the pulmonary system. Because sound speed is inversely proportional to the square root of gas density in free gas, but not in porous media, we measured the effect of air and Heliox (80% He-20% O2) breathing on pulmonary sound transmission in six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…A number of studies have confirmed Rice's findings in lungs inflated in the range from residual volume to total lung capacity (7,8,10,11,17). The upper and lower limits of this range are of particular clinical significance, because compelling evidence shows that injury to the lungs during mechanical ventilation can be attributed to the effects of both overinflation, or volutrauma (5), and underinflation, or atelectrauma (18), in which there is repetitive opening and closing of underexpanded and unstable air spaces.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…A number of studies have confirmed Rice's findings in lungs inflated in the range from residual volume to total lung capacity (7,8,10,11,17). The upper and lower limits of this range are of particular clinical significance, because compelling evidence shows that injury to the lungs during mechanical ventilation can be attributed to the effects of both overinflation, or volutrauma (5), and underinflation, or atelectrauma (18), in which there is repetitive opening and closing of underexpanded and unstable air spaces.…”
mentioning
confidence: 75%
“…A key aspect of our study design was to introduce sound directly to the lung surface, rather than via the airway, the route of entry for sound in most earlier studies using isolated lungs (8,17) or using intact animals (4,15) and humans (1,6,10). Although studies utilizing airway entry of sound report that lung inflation has an effect on the velocity of sound from its point of entry at the airway opening to the surface of the lung or chest wall, interpretation of results requires assumptions about the pathway that sound takes through the respiratory system (1,8).…”
Section: Critique Of Methodsmentioning
confidence: 99%
“…Studies in healthy humans have established that the mouth-to-chest transit time of an acoustic wave is 1.5-5 ms, corresponding to a velocity of 60-80 m/s, considerably slower than the speed of sound in air, and that the amplitude of sound transfer decreases gradually with increasing frequency (6). Although the exact pathway of sound propagation through the bronchial tree and lung parenchyma is not known, low frequencies are believed to exit the central airways and travel along tissue paths, whereas higher frequencies are transmitted to more peripheral airways (5,14).…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in healthy humans and in patients with chronic lung disease indicate that sound energy introduced into the airway can be detected on the surface of the chest and that the transfer of such energy can be quantified in terms of amplitude and wave speed (5,6,15). An experimental study by Donnerberg et al (3) showed that the amplitude of sound transmission through the respiratory system is greater in congested lungs than in normal lungs and that this change is proportional to the lung wet-to-dry weight ratio.…”
mentioning
confidence: 99%
“…In addition, changes in physical properties of breathing gas mix tures (BGMs) make it possible to clarify some funda mental aspects of the physiology and biomechanics of breathing, in particular, formation of the respiratory noises. Nevertheless, studies of this kind are scanty [1][2][3]. It has been recently demonstrated [4] that an acoustic parameter, namely, the duration of tracheal noises of forced exhalation (FE) has a diagnostic value for detecting adverse changes in the lung function after diving with closed type equipment; these are changes presumably related to hyperbaric hyperoxia [5].…”
mentioning
confidence: 99%